Association between meal-specific daily protein intake and lean mass in older adults: results of the cross-sectional BASE-II study. Issue 3 (8th May 2021) - Nikolov, Jivko; Norman, Kristina; Buchmann, Nikolaus; Spranger, Joachim; Demuth, Ilja; Steinhagen-Thiessen, Elisabeth; Spira, Dominik; Mai, Knut
ABSTRACT: Background: Adequate total and meal-specific protein intake is considered an important prerequisite to preserve appendicular lean mass (ALM) in older adults and to prevent sarcopenia. Objectives: We analyzed the meal-specific protein intake across the main meals between participants with normal vs. low ALM to BMI ratio (ALMBMI ). Methods: 782 participants [59.6% men; median 69 (IQR: 65, 71) y] of the Berlin Aging Study II have been included in this analysis. ALM was assessed by dual X-ray absorptiometry. Low lean mass was defined as ALMBMI using recommended sex-specific cut-offs. A 5-day nutritional protocol was used to assess total and meal-specific protein intake. Results: Median total protein intake was 0.89 (IQR: 0.74, 1.05) g/kg/d body weight (BW) in participants with low ALMBMI and 1.02 (IQR: 0.86, 1.21) g/kg BW in participants with normal ALMBMI ( P < 0.001). Daily protein intake at breakfast was similar in both groups [0.23 (95% CI: 0.20, 0.26) vs. 0.24 (95% CI: 0.23, 0.26) g/kg BW; P = 0.245]. Subjects with low ALMBMI reported a lower protein intake at lunch and dinner compared with those with normal ALMBMI [0.29 (95% CI: 0.27, 0.32) vs. 0.35 (95% CI: 0.34, 0.36) g/kg BW; P = 0.001 and 0.32 (95% CI: 0.30, 0.35) vs. 0.36 (95% CI: 0.35, 0.37) g/kg BW; P = 0.027, respectively]. In a stepwise regression model, a higher total protein intake was positively associated with ALMBMI [ß = 0.10 (95% CI: 0.07, 0.13) P < 0.001]. The protein intake at dinner was positively associated with ALMBMI [ß = 0.14 (95% CI: 0.08, 0.19) P < 0.001] irrespective of protein intake at breakfast and lunch. This association disappeared after additional adjustment for total protein intake. Conclusion: Our data highlight an association of total protein intake and ALMBMI in older adults. Although current data support an association of high ALMBMI with protein intake at dinner in particular, this was not independent from total protein intake and the findings do not allow a conclusion on causality.